Renal resistive index in normal adults in Ibadan, South western Nigeria: a preliminary report. (2010)
"Colour Doppler sonography is used for visualization of blood flow,non-invasive evaluation of vascular resistance and measurements of velocities in renal and intrarenal arteries. Its usefulness in the evaluation of the kidneys ranges from the diagnosis of renal arterystenosis and renovascular disease to the assessment of intrarenal hemodynamics in several different pathological conditions such as essential hypertension, acute and chronicrenal failure, pre and post transplant assessment and graft:rejection. Objective:To determine the normal value of Renal Resistive Index in a healthy group of individuals in order to compare findings with those in existing literature and to serve as a normogram among Nigerians. Materials and Methods: Colour duplex Doppler sonography of interlobar arteries was performed in 68 patients with normal blood pressure, normal blood sugar and no known renal disease or any significant medical condition with normal B-mode sonography of their kidneys. The mean renal resistive index of the interlobar arteries was compared on the right and left, males and females and correlated with age, height, body mass index and renal volume. Results:The mean renal resistive index was 0.56 (±0.04) in the right and left kidney. No difference in mean was seen between the males and females. No significant correlation was seen with age ,height ,body mass index and renal volume. Conclusion: This study has provided normative value of renal resistive index' in a Nigerian population and established this data for use in future studies. "